PERSEPSI MEREK DALAM ERA CANCEL CULTURE: STUDI KASUS STARBUCKS DAN K-POP - Wulandari Dewi, Ni Putu Eka Budi Pradnya; Agustin, Chaerani (Ensiklopedia of Journal, 2025)
This article discusses the response of the K-Pop fan community to the phenomenon of collaboration between Starbucks and NCT. This collaboration has sparked significant controversies. In recent years, major companies such as Starbucks have faced considerable challenges due to social and cultural dynamics within the realm of social media. One case that has drawn attention is how K-Pop fans can shape public opinion on a large scale regarding the Starbucks brand through social media platform X. This article further examines the patterns of digital activism in the boycott actions carried out by K-Pop fans in response to the Starbucks and NCT collaboration. The study also explores audience analysis regarding K-Pop fans' perceptions of NCT as a result of the collaboration, which triggered public tension. For its research method, this study employs netnography, through which communities can construct and express themselves within digital spaces. Sample posts relevant to the topic were identified through posts on X (Twitter) and analyzed in depth. The results of this study show that criticism from K-Pop fans played a role in restoring Starbucks’ reputation.Keywords: Starbucks, K-Pop fans, Social Media, Brand Response, Reputation Management